Axial resolution and imaging contrast enhancement in inverted light-sheet microscopy by natural illumination modulation - Wang, Zhi; Qiao, Wei; Jiang, Tao; Chen, Siqi; Lu, Bolin; Ning, Kefu; Jin, Rui; Gong, Hui; Yuan, Jing (Frontiers in Neuroscience, 2022)
Oblique light-sheet microscopy (OLSM) is widely employed for fast large-volume imaging of biological tissue. However, the scattering especially in uncleared samples, and the divergent propagation of the illumination beam lead to a trade-off between axial resolution and imaging depth. Herein, we propose naturally modulated OLSM (NM-OLSM) as a technique to improve axial resolution while simultaneously maintaining the wide field-of-view (FOV), and enhancing imaging contrast via background suppression. Theoretical derivations, simulations, and experimental imaging demonstrate 15% axial resolution increases, and five-fold greater image contrast compared with conventional OLSM. Therefore, NM-OLSM allows convenient imaging quality improvement for uncleared tissue and could extend the biological application scope of OLSM.